Characterization of motorcycle accident victims attended by the mobile emergency service (SAMU-192), Recife, Pernambuco State, Brazil - 10.4025/actascihealthsci.v34ispec.11524 - Luciana Melo da Silva; Rafaella Aarujo Correia; Betise Mery Alencar Sousa Macau Furtado; Cristine Vieira do Bonfim (Universidade Estadual de Maringá, 2012)
This study described the epidemiological characteristics of victims of accidents involving motorcycles, attended by the Mobile Emergency Service (SAMU-192) in the city of Recife (PE) in 2006. This is a descriptive cross-sectional study that analyzed a sample of 703 cases. The results showed that 81.8% were male, aged 20 to 29 years. It was noted that 406 of them were wearing a helmet at the time of the accident. The accidents occurred most frequently on Sundays (19.3%) between 18:00 and 24:00 hours (0.28%). The extremities were the most affected body segment, with 341 occurrences. Regarding the severity of injuries, it was found that 37.6% were superficial or mild (scrapes, cuts and bruises). These results demonstrate the need for educational campaigns to encourage the use of personal protective equipment among motorcyclists. The best way to reduce the risks and damages from motorcycle accidents is through primary prevention. For this, are needed integrated intersectoral actions aimed at reducing the incidence and severity of injuries.